The THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURES AND ENVIRONMENTAL PERFORMANCE ON FINANCIAL PERFORMANCE IN THE MINING SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - Devi Ayu Putri; Gresy Santha Laura Hasibuan (Jurnal Ekonomi, 2023)
The purpose of this study is to ascertain the impact of CSR and environmental performance disclosure on financial performance in the mining sector listed on the Indonesian stock exchange in 2017–2020. 47 mining businesses that were listed on the Indonesian stock exchange between 2017 and 2020 make up the study's population. 32 statistics from the study's sample of 8 companies over a 4-year period are presented. Associative methodology will be used in this kind of research. Quantitative data are the type of data used in this study, while secondary data are the data source. Multiple linear regression analysis using SPSS version 25 was the method of data analysis used in this study. The documentation technique is the method of data collection that is employed. The results of this study show that the variable environmental performance (X2) and the variable corporate social responsibility (X1) each have a positive and significant effect on financial performance. The variable corporate social responsibility (X1) and environmental performance (X2) also have a positive and significant effect on financial performance individually (Y). All hypotheses are accepted because these results are consistent with the established ones.